2022
DOI: 10.3390/cancers14051258
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Metastatic Bone Disease in the Appendicular Skeleton: A Population-Based Study

Abstract: Background: Population-based studies of patients with bone metastases in the appendicular skeleton (aBM) requiring surgery for complete or impending fracture are rare. In this epidemiologically-based observational study we created a large population-based cohort of patients treated for aBM, aiming to: (1) monitor possible time-related changes of the incidence of surgical treatment of aBM-lesions, (2) examine differences in the population and care of patients treated at different treatment centers and (3) exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Instead, they found fast-growth primary cancers, visceral metastases, no chemotherapy after surgery, and implant type to be risk factors for death. The described increased risk of 30-day mortality for patients having IF is probably a result of bias in the selection of surgical treatment for patients with a poor prognosis who tend to undergo less invasive surgery [ 18 ], as illustrated in Table 1 , describing differences between patients treated with EPR and IF. Furthermore, patients undergoing IF for aBM in the femur may be limited in immediate weightbearing due to the painful lesion if not removed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, they found fast-growth primary cancers, visceral metastases, no chemotherapy after surgery, and implant type to be risk factors for death. The described increased risk of 30-day mortality for patients having IF is probably a result of bias in the selection of surgical treatment for patients with a poor prognosis who tend to undergo less invasive surgery [ 18 ], as illustrated in Table 1 , describing differences between patients treated with EPR and IF. Furthermore, patients undergoing IF for aBM in the femur may be limited in immediate weightbearing due to the painful lesion if not removed.…”
Section: Discussionmentioning
confidence: 99%
“…We found a 30-day survival probability of 85% (CI 81–88), slightly lower than found in our previous study [ 11 ]. This is probably explained by the present study including patients treated at secondary surgical centers, who are shown to have significantly poorer survival than patients treated at a highly specialized center [ 18 ]. Tsuda et al [ 10 ] report a 30-day mortality after surgery for metastatic lesions in the femur of 2.6%, which is considerably lower than ours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations